Pemberdayaan Pemanfaatan Qris pada Masyarakat Pelaku UMKM di Kota Palangka Raya - Lulu Naimatul Khairiah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This service program aims to provide introduction and understanding to the community as Micro, Small, and Medium Enterprises in Palangka Raya City in using non-cash payments or QR, because the QR payment method is considered very effective in modernizing the payment system and can increase the efficiency of the payment process in the MSME business world. The process of implementing this service uses a qualitative activity method with a type of interactive training that involves MSME actors directly, where MSME actors are given a brief understanding of the introduction and procedures for using QR technology as one of the payment methods in Business. The results of the implementation of this service activity show that there is a lot of interest from MSME actors to use QR as a means of payment, because of the minimal risk of errors from the administration of financial calculations, as well as the ease of use and can reduce the circulation of banknotes. By adopting QR in business, it can help MSMEs to have a wider market reach and can increase their selling competitiveness in the wider digital era. The circulation of the use of QR as one of the payments for MSME actors, proves that community empowerment through the use of QR Codes in Palangka Raya City is a success of the empowerment program.